Monetary Policy in Turkey after Central Bank Independence - Refet S. Gürkaynak; Zeynep Kantur; M. Anil Tas; Seçil Yildirim (Center for Economic Studies and ifo Institute (CESifo), 2015)
We present an accessible narrative of the Turkish economy since its great 2001 crisis. We broadly survey economic developments and pay particular attention to monetary policy. The data suggests that the Central Bank of Turkey was a strong inflation targeter early in this period but began to pay less attention to inflation after 2009. Loss of the strong nominal anchor is visible in the break we estimate in Taylor-type rules as well as in asset prices. We also argue that recent discrete jumps in Turkish asset prices, especially the exchange value of the lira, are due more to domestic factors. In the post-2009 period the Central Bank was able to stabilize expectations and asset prices when it chose to do so, but this was the exception rather than the rule.
Keywords: E52; E62; E31; E32; E02; 330; Turkey; CBRT; monetary policy; fiscal policy